Scarcity Effects of Quantitative Easing on Market Liquidity : Evidence from the Japanese Government Bond Market - Han, Fei.; Seneviratne, Dulani (Washington, D.C. : International Monetary Fund, 2018)
Quantitative easing could improve market liquidity through many channels such as relaxing bank funding constraints, increasing risk appetite, and facilitating trades. However, it can also reduce market liquidity when the increase in the central bank's holdings of certain securities leads to a scarcity of those securities and hence higher search costs in the market. Using security-level data from the Japanese government bond (JGB) market, this paper finds evidence of the scarcity (flow) effects of the Bank of Japan (BOJ)'s JGB purchases on market liquidity. Moreover, we also find evidence that such scarcity effects could dominate other effects when the share of the BOJ's holdings exceeds certain thresholds, suggesting that the flow effects may also depend on the stock.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet